Commentary on the 2014 BP Guidelines from the Panel Appointed to the Eighth Joint National Committee (JNC 8) - Reisin, Efrain (American Society of Nephrology, 2014)
The recently published article “2014 Evidence-based guideline for the management of high blood pressure in adults: Report from the panel members appointed to the Eighth Joint National Committee (JNC 8)” (James et al., JAMA 311: 507–520, 2014) has generated considerable controversy. In this commentary, we evaluate the document and compare the recommendations contained within it with those of the JNC 7 and other national and international guidelines. The evidence quality rating approach followed by the article “2014 Evidence-based guideline for the management of high blood pressure in adults: Report from the panel members appointed to the Eighth Joint National Committee (JNC 8)” (James et al., JAMA 311: 507–520, 2014) disqualified nearly 98% of previous studies from review; as a result, some of the key recommendations were on the basis of expert opinion alone. We are especially concerned that the recommendation to raise the systolic/diastolic BP levels at which treatment is initiated to ≥150/≥90 mmHg in adults≥60 years old may affect cardiovascular and renal health in these patients. Additionally, we recommend that hypertension guidelines should be updated every 3–4 years with a fresh approach to the definition of target BP levels, the use of modern technology in the diagnosis of hypertension, and the treatment of hypertension in special populations not addressed in earlier guidelines.